Understanding the Association of Subjective Perception and Emotional Resentment With Micro- and Macro-Level Violence: A Multilevel SEM Examination of Relative Deprivation Theory - Park, Seong-Min (Crime & delinquency, 2025)
Criminological theories suggest that economic deprivation elevates violence in societies at both micro and macro levels. Relative Deprivation Theory constructed this causal framework by introducing pathways from objective deprivation to violence through mediating subjective perceptions and emotional resentments. This study tests these interactive pathways by building and examining stepwise multilevel structural equation models. We sampled 2,040 residents in South Korea using pair-matching stratified sampling and conducted face-to-face interviews. Findings suggest that subjective perception and emotional resentment play significant roles in understanding the association between economic deprivation and violence. These findings signify that criminologists should consider individual cognitive interpretations and social/cultural backgrounds when investigating the impact of economic deprivation.